Convents and conspiracies: a study of convent narratives in the United States, 1850-1870 - McGowan, Catherine (The University of Edinburgh, 2009)
In recent years, historians studying the United States in the mid-nineteenth century have made increasing use of popular writings to identify attitudes and beliefs. One genre of writing which has been largely overlooked by scholars of history is the convent narrative. These texts criticized convents and claimed that American nuns suffered imprisonment and abuse. Numerous examples of this genre, including both avowedly fictional novels and purported real-life autobiographies, were published in the United States between 1850 and 1870. Detailed study of these works uncovers a rich seam of evidence of popular attitudes to a range of political, religious and social forces, including republicanism, Catholicism, immigration, urbanization, industrialization, slavery and the role of women. This study analyzes and compares the themes, ideologies and techniques found in these texts. It will relate these to their wider context, and will examine the role the texts played in transmitting and reinforcing the beliefs and opinions of their authors. Close study of the narratives reveals that their authors were primarily concerned, not with the religious implications of convents and Catholicism (although these did alarm these authors), but, first and foremost, with the safety and stability of the American republic. The creators of convent narratives believed that the republic was under siege from anti-republican forces working to undermine the American way of life on a number of different fronts. These concerns are manifested repeatedly in the convent narratives. Where previously this genre has been overlooked by historians, except as a straightforward manifestation of lurid and sensationalistic anti-Catholic nativism, this study analyzes the deeper ideals and ideologies which these documents reveal, and establishes a basis for further exploration, both of the convent narrative genre in itself and of popular and populist literature in general.
Keywords: History